A comparative study of the Morphosyntaz and Phonetics of Town Bemba and Standard Bemba of the Copperbelt Zambia - Kabinga, Moonde (Linguistics, 2014)
For many years now, the status of Town Bemba (TB) has been fuzzy in its descriptions, as no specific framework has been used in characterising the language variety. TB has been regarded as an urban variety spoken in the townships of the Copperbelt province, Zambia. It had also been perceived as a 'secret language' or 'mixed jargon' used by male migrant workers on the mine, but today, it is used by males and females across the board, and also tends to be used as first language (L1) for offspring raised there. This research attempts to investigate the status of TB. It will also make observations of any significant differences between TB and Standard Bemba (SB) through linguistic markers and style of speech by the informants. The comparative analysis will help in assessing the extent to which TB has deviated from SB. The data for morphosyntax, socio-phonetic and lexical analyses was collected through one-on-one interviews and two TB music lyrics. Twenty speakers of TB and SB were interviewed in this research. For data analysis three theoretical frameworks were used namely; Myers-Scotton's Matrix Language Frame Model (MLF) for the morphosyntax data; socio-phonetics using Praat and Normalisation of vowels for phonetic data; and a linguistic characterisation of language varieties were used to characterise TB and establish its status. The results show that TB is quite similar to the base language SB and exemplifies general characteristics that are more similar to Tsotsitaal. The difference is that the former (TB) uses one base language (SB) with heavy borrowing and assimilations from English mainly and a bit from local languages like Nyanja, and Afrikaans; the variety is used by people of different ethnic backgrounds, its commonly used in everyday life among educated and non-educated male and female speakers. TB also has been able to preserve many forms associated with more traditional Bemba and at the same time shows changes in some of its lexical and grammatical forms, mainly simplification. Tsotsitaal in comparison is associated with many base languages but behaves similarly to TB in other ways. In this regard, I suggest that TB be referred to as another type of an urban variety that is moving towards being a new language because it is more than a 'style' (Hurst 2008) like Tsotsitaal.